Perkembangan Keuangan Syariah dan Pertumbuhan Ekonomi di Indonesia: Analisis Hubungan Jangka Panjang dan Jangka Pendek: The Development of Islamic Finance and Economic Growth in Indonesia: An Analysis of Long-Term and Short-Term Relationships - Azwar Azwar; Arif Mashuri; Jamaluddin Majid (HISAB: Jurnal Akuntansi Lembaga Keuangan Syariah, 2025)
This study aims to analyze the short-run and long-run relationship between sukuk development and economic growth in Indonesia. The research employs a quantitative approach using annual time series data covering the period 2003–2022. The dependent variable is Gross Domestic Product (GDP) per capita (current US$), while the independent variable is the value of Sukuk Outstanding (in billion rupiahs). The analysis utilizes the Autoregressive Distributed Lag (ARDL) model to examine both the long-term and short-term linkages between the two variables. The estimation results indicate that, in the long run, sukuk has a positive and significant effect on economic growth, confirming that an increase in sukuk issuance can strengthen national economic activity through the financing of productive, asset-based projects. In the short run, the Error Correction Model (ECM) results reveal an error correction coefficient of -0.084852, which is significant at the 1% level, implying an adjustment mechanism of approximately 8.48% per period toward long-run equilibrium. Although temporary negative effects are observed from previous sukuk issuances, the findings suggest that the market possesses a gradual self-correcting capacity. This study underscores the strategic role of sukuk in supporting sustainable economic growth in Indonesia, in line with Islamic finance principles that emphasize justice, stability, and social welfare.